The Listeria monocytogenes exopolysaccharide significantly enhances colonization and survival on fresh produce - Fulano, Alex M.; Elbakush, Ahmed M.; Chen, Li-Hong; Gomelsky, Mark (Frontiers in Microbiology, 2023)
Fresh produce contaminated with Listeria monocytogenes has caused major listeriosis outbreaks in the last decades. Our knowledge about components of the listerial biofilms formed on fresh produce and their roles in causing foodborne illness remains incomplete. Here, we investigated, for the first time, the role of the listerial Pss exopolysaccharide (EPS) in plant surface colonization and stress tolerance. Pss is the main component of L. monocytogenes biofilms synthesized at elevated levels of the second messenger c-di-GMP. We developed a new biofilm model, whereby L. monocytogenes EGD-e and its derivatives are grown in the liquid minimal medium in the presence of pieces of wood or fresh produce. After 48-h incubation, the numbers of colony forming units of the Pss-synthesizing strain on pieces of wood, cantaloupe, celery and mixed salads were 2-12-fold higher, compared to the wild-type strain. Colonization of manmade materials, metals and plastics, was largely unaffected by the presence of Pss. The biofilms formed by the EPS-synthesizing strain on cantaloupe rind were 6-16-fold more tolerant of desiccation, which resembles conditions of whole cantaloupe storage and transportation. Further, listeria in the EPS-biofilms survived exposure to low pH, a condition encountered by bacteria on the contaminated produce during passage through the stomach, by 11-116-fold better than the wild-type strain. We surmise that L. monocytogenes strains synthesizing Pss EPS have an enormous, 102-104-fold, advantage over the nonsynthesizing strains in colonizing fresh produce, surviving during storage and reaching small intestines of consumers where they may cause disease. The magnitude of the EPS effect calls for better understanding of factors inducing Pss synthesis and suggests that prevention of listerial EPS-biofilms may significantly enhance fresh produce safety.